DEVELOPMENT OF CHITOSAN-FILLED POLYURETHANE COMPOSITES AS ANTIBACTERIAL COATING PAINT - Nurlaili, N (Jurnal Sains dan Teknologi Reaksi, 2023)
Polyurethanes are generally made from petroleum-based polyols, but the current state of petroleum is depleting. The availability of petroleum, which is currently decreasing, encourages other parties to look for new alternatives. One alternative that can be used is palm oil. Technological developments that continue to increase are now also a reference for the development of antibacterial polyurethane coating paints which are carried out by adding another filler, namely chitosan. This study aims to determine the effect of variations in the weight of chitosan as an antibacterial agent through morphological analysis of Surface Scanning Electron Microscopy (SEM), heat resistance test with Thermo Gravimetry Analyzer (TGA), and Bacterial activity test. The analysis process was carried out with variations in the weight of chitosan (2; 3; 4) % w/w). The test results showed that the best polyurethane coating paint was with a variation of 4% w/w chitosan filling. This is because the more addition of chitosan, the better it will be in inhibiting bacterial activity.Keywords : Chitosan, Composites, Polyols, Polyurethanes, TDI